FEATURES OF COGNITIVE ACTIVENESS OF UNIVERSITY TEACHERS IN RUSSIA - Nikolaev, Alexej; Kolbasova, Irina; Shlat, Natalia; Suvorova, Evgenia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
There has been a decrease of the activeness in the sphere of self-improvement among specialists. It can be assumed that this happens with university teachers as well, and the reason for this might be the fall of their cognitive activeness. The author of the article determines the particularity of the cognitive activeness, its most valuable indicators, as well as their psychological factors. The objective is to reveal the peculiarities of cognitive activeness for further scientific justification of the ways of its development. The questionnaire and the experiment methods were used, the cognitive activeness of the teachers was measured with the scale-type survey, worked out by J. J. Zhukov; the satisfaction with the performance was measured with the expert assessments survey, worked out by G. V. Lozovaja; the pedagogical abilities, the motives of professional activity, the successfulness of the performance and the adaptation to it were determined by the A. N. Nikolaev´s surveys. The main results are the following: the components of cognitive activeness dominate – the integration of educational material, supra-situational activity, the interest in cognition. The components of cognitive activeness have an impact on all indicators of teachers' adaptability. Three types of teachers have been identified: those motivated to the success of their activity; those motivated to the process itself; and those who are passionate about their activities. These types correspond to the results of the factor analysis with factors that are focused on the profession and self-improvement through cognitive activeness, on the activity preference based on one´s interests, and on the success of the activity according to one´s abilities.